Usulan Model Pengukuran Kinerja Rantai Suplai untuk Meminimalkan Keterlambatan pada Pengiriman ONS - Wahyudi Sutopo; Widha Windhira; Yuniaristanto - (Performa: Media Ilmiah Teknik Industri, 2008)
CV. ABC is one of company that offers services on package delivery. Based on observation wasconducted during the months of January up to August in 200x was found tardiness around 2.5% average per month.The type of delivery service that having the highest level of tardiness is the ONS (Overnight Service). This research is aim to design a model of performance measurement and to compile system proposal of supply chain to minimize the tardiness of ONS’s system in CV. ABC. The model was developed from previous result such as Bowersox & Closs (1996), Simchi-Levi et. al. (2000) dan Beamon (2004) that are performance measure model by involving the four measurement variables: delivery to commit date, order fulfillment leadtime, response time, and make time. The result of the data analysis describes that the actual performance of the four variables still in below the target. Therefore, it is suggested to conduct a restructurization to redesign the ONS system itself. Proposal of designing based on Beamon theory to develop operation improvement. The processing time during the packages stay in ABC's branch of Solo needs a very long duration passing by the definite target, so it is recommended: 1). to eliminate the uneffective process, 2). to merge the processes that are possible to be handled together, 3). to use better facility to shorten the length of the process, and 4). to apply a new documentation system.